P2RY1 and P2RY12 polymorphisms and on-aspirin platelet reactivity in patients with coronary artery disease - TIMUR, AYSE ANIL (2012)
INTRODUCTION: Association of P2RY1 and P2RY12 polymorphisms with on-aspirin platelet reactivity was investigated. MATERIALS AND METHODS: Platelet reactivity was assessed by light transmission aggregometry and TxB(2) assay in 423 CAD (coronary artery disease) patients on aspirin. High residual platelet reactivity (RPR) was defined by≥20% and ≥70% maximal aggregation stimulated with 0.5 mg/mL AA and 10 μM ADP, respectively. Moderate RPR was considered aggregation ≥20% with AA, ≥70% with ADP, or ≥1 ng/mL stimulated TxB(2). Fourteen P2RY1 and 35 P2RY12 SNPs were genotyped. RESULTS: High RPR was detected in 24% of the patients. Moderate RPR was observed in 31% with AA, 57% with 5 μM ADP, and 82% with 10 μM ADP. Stimulated TxB(2) was ≥1 ng/mL in 23% of patients. P2RY12 SNP rs9859538 was associated with high RPR (OR=2.16, 95% CI=1.24–3.75, p-value=0.004). Four P2RY12 SNPs, rs1491974, rs10513398, rs3732765, and rs10935841, showed association with moderate RPR (OR=1.79–2.94, p-value=0.04–0.028), while five, rs7615865, rs1388623, rs1388622, rs7634096, and rs7637803, were associated with low RPR (OR=0.50–0.55, p-value=0.008–0.026), following ADP stimulation. TxB(2) level <1 ng/mL was linked to five P2RY1 SNPs, rs1439010, rs1371097, rs701265, rs12497578, and rs2312265, (OR=0.36–0.54, p-value=0.003–0.039). CONCLUSIONS: Polymorphisms in P2RY1 and P2RY12 are associated with on-aspirin platelet reactivity in CAD patients.